The South China Sea: A history of disputes - Cruz Aguilar, Sérgio Luiz [UNESP]; Mendes Fakhoury, Renato Matheus (Universidade Estadual de Ponta Grossa (UEPG), 2019)
The South China Sea is disputed by several surrounding Nations. Disputes over the region are long-standing, however, they have intensified over the last few decades due to the strategic importance of the region related to its significance as a trade route and its oil and gas reserves. The article presents the geostrategic importance of the South China Sea and the history of disputes in the area.
Mar do Sul da China: Um histórico de disputas
Keywords: Asia; International Disputes; South China Sea